The effect of composite edible coatings on the postharvest quality of “Hass” avocado fruit treated at different harvest maturities - Ngubane, Sibonelo; Tesfay, Samson Z.; Magwaza, Lembe S.; Mditshwa, Asanda (Frontiers in Sustainable Food Systems, 2024)
Edible coatings play a critical role in reducing postharvest losses during storage and supply chain of horticultural commodities. The present study evaluated the efficacy of different concentrations of moringa leaf extract (MLE) combined with carboxymethyl cellulose (CMC) edible coating in preserving the quality and extending the shelf life of “Hass” avocado. Fruit were harvested at different stages of maturity and evaluated by dry matter content. Different concentrations of moringa (8 and 16%) extracted with chilled ethanol (100%) and functionalized with CMC (5%), were used to treat the fruit. Treated fruit were then stored at 5.5 ± 1°C and 90 ± 5% RH for 28 days plus an additional 7 days at 23°C. The changes in physicochemical and biochemical fruit attributes were evaluated at weekly intervals. The application of moringa and CMC-based edible coatings preserved the phenolics, flavonoids, and antioxidant activity of “Hass” avocado. The treatments significantly (p < 0.05) reduced the loss of weight and firmness. Furthermore, treated fruits were found to have a delayed color change and reduction in sugar concentration, particularly mannoheptulose, compared to the control treatment. Therefore, edible coatings prepared by combining CMC and MLE could be the best alternative for substituting the currently used health-compromising synthetic chemicals.